Pengaruh Information Overload terhadap Perilaku Penghentian Penggunaan pada Social Networking Service (SNS) - Ayu Pramadita Dewi; Diah Priharsari; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Pandemic of COVID-19, which is a new type of virus, has brought so many changes in any aspects of people's life. The era of pandemic causes everyone to need the latest information. Various sources of digital media can be accessed by everyone to get information. One of the media to get information is Social Networking Service (SNS). The high flow of information that cannot be controlled in SNS causes Information Overload for the users. Information Overload is a condition where the user cannot process the information contained in the SNS because too much information available. The aim of this study is to determine whether Information Overload has an effect on SNS Exhaustion and whether SNS Exhaustion has a positive effect on Discontinuous Usage Of SNS. The technique of data collection in this study is a survey. Data processing in this study using Structural Equation Modeling Covarianced Based (SEM-CB). The use of SEM is to test the relationship between variables. SEM-CB is used to confirm the existing theory from the references of this study. The sample need for this research is the users of SNS who have read informations about COVID-19. From the survey, the sample data obtained in this study were 332 SNS users. The result of this study indicate that Information Overload has an impact on SNS Exhaustion and SNS Exhaustion has an Impact on Discontinuous Usage Of SNS.